The influence of geostrophic strain on oceanic ageostrophic motion and surface chlorophyll - Zhengguang Zhang (Nature Portfolio, 2019)
The ocean’s swirling eddies are known to influence primary productivity, yet understanding of these processes has been hampered by a lack of resolution. Here the authors combine in-situ drifter, altimeter-based feature tracking, and satellite chlorophyll data to quantify how phytoplankton respond to surface mesoscale phenomena across the globe.